Aspect-Opinion Identification and Classification Using Custom Heuristic Rules - Kadam, TU; Kaur, P (International Journal of Computer Sciences and Engineering, 2025)
Users opinion about different entities forms the huge repository of data over internet. It is highly impossible to accurately monitor and find what actually a user wants to say about an entity from this large amount of data. Data analyst these days concentrates on finely analyzing opinions about particular entity and for this reason the extraction of aspects and its corresponding opinions of that entity are important. This work concentrates on identifying aspects and their corresponding opinion from the provided user opinions which helps to obtain fine grained knowledge about the entity. To obtain aspects and related opinions custom heuristic rules are created by using regular expression on the parts-of-speech tagging. The created rules are provided to Stanford natural language processing (SNLP) classifier and finds association of aspect words and opinion words from the opinion corpus. The classification is done by SNLP classifier and Naïve Bayes (NB) classifier. Identification of aspects and aspect specific opinions are accurately obtained using custom heuristic rules applied over SNLP compared to NB.